Effective Use of Topical Ketamine in Managing Acute Post‐Operative Pain Following Fournier's Gangrene Surgery: A Case Report - Aariya Srinivasan; Madeline Dow; Renata Barbosa Dos Santos; Sabry Ayad (Clinical Case Reports)
ABSTRACT Topical ketamine effectively reduces acute postoperative pain following Fournier's gangrene surgery, allowing for opioid reduction and enhancing patient comfort during wound care. Its use provides an alternative to systemic opioids, minimizing side effects and dependency risks. Further research is needed to optimize dosing and confirm outcomes.